Structural works of column and staircase for water tank / Muhammad Haziq Azhad Ahmad Nizam - Ahmad Nizam, Muhammad Haziq Azhad (Universiti Teknologi MARA, Perak, 2022)
A water tank is a storage container for water. Water tanks are used to store water for a variety of purposes, including drinking water, irrigated agriculture, fire suppression, agricultural farming, both for plants and animals, chemical manufacture, food preparation, and a variety of other applications. The water tank should be place at the high place to easier the water to flow to the consumer, so the water tank tower should be built to place the water tank. Therefore, this report will discuss about the components of the tower which are column and staircase. The objective of this report is to identify the type of material and equipment used to build these structures. It will focus on the typical material used to ensure that the column and staircase that be built are strong enough to receive the loads. On top of that, the methods of building these structures are also will be highlighted in this report so that the steps of building them are correct and in orderly manner. This report also will discuss about the problems that happened along the construction process to find the solutions to overcome them. These solutions will make the next construction process run smoothly without the same problems happen again and with that, it will make the structure of the tower in a good condition and will last longer to provide the better place for water tank to flow the water for a long time.